Heritabilitas, Karakterisasi, dan Analisis Clustergram Galur-galur Padi Dihaploid Hasil Kultur Antera - Anshori, Muhammad Fuad; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Ardie, Sintho Wahyuning; Suwarno, Willy Bayuardi; Safitri, dan Heni (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Doubled haploid rice formation through anther culture becomes one of the alternatives in the plant breeding. The lines need to be characterized, clustered, and selected. This study aimed at determining heritability, characters, and cluster of doubled haploid lines obtained from anther culture. This experiment was conducted at IPB Rice Field Experiment Station, Darmaga, Bogor from October 2016 until January 2017. The experiment was managed according to randomized complete block design (RCBD) with 3 replications and genotype as the single factor treatment. Genotypes used were 60 genotypes consisting of 56 doubled haploid lines and 4 control varieties. The controls were Ciherang, Inpara 5, Inpari 29, and Inpari 34 Salin Agritan. The results showed that all characters have significant effect and high heritability (above 60%), so they could be used as a selection character. The tested genotypes could be grouped into three main groups. The first group consisted of 11 genotypes, the second group consisted of 44 genotypes, and the third group consisted of 5 genotypes. The main group determinant characters were productive tillers, percentage of filled grain number, plant height, panicle length, and weight of 1,000 grains. The number of filled grain and productive tillers can be used as selection characters together with yield potential.